FORMATION OF INDEPENDENT THINKING OF STUDENTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The modern system of higher education should be considered as the most important institution of socialization of the individual, in which training and education is a single process aimed at training highly educated, widely erudite, cultural, creative thinking specialists.